The economics of East Coast Fever Immunization in Uganda. - Laker, C.D. (University of Nairobi, 1993)
The livestock sub-sector of the agricultural sector plays an important role in the economic and social development of Uganda. It contributes about 30 percent of agricultural Gross Domestic Product. The sub-sector is very important in Mbarara District where it is estimated that approximately one million head of cattle are found. This cattle population is approximately 25 percent of the national herd. However, animal production is limited by, among other things, the widespread incidence of tickborne diseases especially East Coast fever (ECF) caused by T. parva and Anaplasmosis caused by A. marginale. East Coast fever causes high case-fatality rates of up to 100 percent. The current costs of ECF chemotherapy per head are estimated at USh 20,0001= (US$ 20) for grade cattle and USh 5,0001= (US$ 5) for indigenous cattle. These different rates are brought about by differences in drugs used, with grade cattle being treated with the relatively more expensive drug Clexon" (parvaquone, Coopers Animal Health) and indigenous cattle being treated with the less costly Oxytetracycline. The current costs of dipping an animal per year are estimated at USh 42001 = (US$ 4.2) for a frequency of once a week immersion, and USh 84001=(USS 8.4) for a frequency of twice a week immersion spent on acaricides alone. Spraying costs are estimated at USh 56001 = (US$ 5.6) and USh 11,2001= (US$ 11.2) for once a week and twice a week application respectively. These cost levels, which are likely to increase with time, are regarded as prohibitive by farmers. A practical method of immunizing cattle against ECF called "Infection and Treatment" method (Radley, 1981) is increasingly being applied by various countries in eastern, central and southern Africa region as a viable alternative to reliance on acaricides alone. Trials were recently conducted in Uganda and are now being assessed. Ex ante analysis of this method in Mbarara District shows that it is an economically viable method to the farmer. Various scenanos B,C, D and E, where animals were assumed to be immunized and acaricide application frequencies reduced by 0 percent, 25 percent, 50 percent and 75 percent respectively were compared with the current control situation (scenario A). Immunization at US$ 4 per cattle head resulted in reduced economic costs by 23.5 percent, 27 percent, 31 percent and 35 percent in grade cattle and by 14 percent, 19 percent, 23 percent and 27 percent in indigenous cattle for scenarios B, C, D and E respectively. Increases in net income are also estimated at 44 percent, 67 percent, 89 percent and 112 percent in grade cattle in scenarios B, C, D and E respectively. For indigenous cattle, net income declined by 0.3 percent in scenario B and then rose by 5 percent, 10 percent and 15 percent in scenarios C, D and E respectively. Immunization would thus appear to have a positive financial impact on the cattle industry in Mbarara District. However, more studies of this nature, taking into account the long term effects and consequences of this method of control on animal production, are required in order to generate comprehensive information to help guide policy formulation on more optimal strategies for the control of tick-borne diseases, particularly ECF, in Uganda.